Hubungan Tingkat Pendidikan Orang Tua dan Motivasi Belajar Siswa terhadap Hasil Belajar Kognitif Siswa Kelas V di MI Zumrotul Wildan Jepara - Ainur Riyadhoh (JEID: Journal of Educational Integration and Development, 2022)
This study discusses the relationship between parents' education level and students' learning motivation on mathematics learning outcomes for the fifth grade students of MI Zumrotul Wildan. This study was conducted with the aim of knowing the relationship between parents' education level and students' learning motivation together with the mathematics learning outcomes of class V MI Zumrotul Wildan students. This study uses quantitative research methods to obtain the significance of the relationship between parental education level and student learning motivation on cognitive learning outcomes in mathematics, while the approach used in this study is correlation. The subjects of this study were 22 students of class V MI Zumrotul Wildan Jepara taken from a representative population. The data analysis technique used is statistical analysis with multiple correlation techniques. The results of this study indicate that 1) there is a positive and significant relationship between Parental Education Levels with Cognitive Learning Outcomes for Class V Mathematics Subjects at MI Zumrotul Wildan 2) there is a positive and significant relationship between Student Learning Motivation and Cognitive Learning Outcomes for Grade Mathematics Subjects. V MI Zumrotul Wildan 3) There is a positive and significant relationship between the education level of parents and students' learning motivation together there are cognitive learning outcomes of students in mathematics, it is shown from the test results through the F test that the F arithmetic value > F table is 5,495 > 3.52 and sig. 0.013 the value is smaller than 0.05. So Ha is accepted and Ho is rejected.